Perceptions and Barriers toward HPV Vaccination among Young Women: A Physiological Perspective - Shami, Hasan; Sajid, Bushra; Nadeem, Arika; Rekha, Chander; Afzal, Asifa; Memon, Farzana Rahim (Journal of Neonatal Surgery, 2025)
Background: Human Papillomavirus (HPV) infection is the leading cause of cervical cancer worldwide. Young women are underserved and under-immunized within the context of an effective vaccine. Inaccuracies, cultural beliefs, lack of knowledge, and access barriers all lead to low uptake. Knowledge of perceptions and barriers is necessary to steer appropriate health promotion strategies. Objectives: To review the perceptions, attitudes and barriers on HPV vaccination among young women with some particular attention to different socio-cultural, financial and information factors impacting acceptance and uptake of the vaccine. Study Design and Settings: A cross-sectional study at Abbasi Shaheed hospital, Karachi, January 2025 to June 2025. Methods: A cross-sectional study was conducted among 120 young women of age group between 18 and 26 years. A structured questionnaire was used to evaluate sociodemographic information, knowledge, perceptions and barriers about the HPV vaccination. Statistical analyses were conducted using SPSS version 24.0. Continuous variables were expressed as the mean ± standard deviation and categorical, as a percentage. Associations were determined by chi-square and independent t-tests, with significance set at p < 0.05. Results: The mean age of 120 subjects was 21.8 ± 2.4 years, who were included in the study. The knowledge about HPV infection was acknowledged by 38% of respondents and only 25% had heard about the vaccine. Key barriers included not knowing about DAA (62%), safety concerns (48%) and cost of DAA therapy (40%). Parental opposition was noted by 30% of the respondents. Women with more than secondary school education were significantly more likely to accept future vaccination (p = 0.02), as well as those who had heard of HPV previously in the bivariate analysis (p = 0.01). Cultural stigma and misinformation were the reasons cited most often for being hesitant to become vaccinated. Conclusions: Lack of awareness, cultural stigma, safety concern and high cost remain barriers to HPV vaccine uptake among young women. Education and prior knowledge were better predictors of vaccine acceptance. To mitigate these barriers is need for targeted health educational programs, affordability measures and a strong support from the healthcare provider. Attending to sociocultural influences and misinformation will facilitate acceptance and reduce disease morbidity from HPV